Fluid and stable: Dynamics of team action patterns and adaptive outcomes. (27th February 2018) - Uitdewilligen, Sjir; Rico, Ramón; Waller, Mary J.
Summary: The current study draws on work in the areas of team adaptation, team compilation, and small groups as complex systems to predict and test relationships between time, taskwork team mental models, team action patterns, and team effectiveness. Three‐person teams performed 9 scenarios of a firefighting simulation distributed over 3 days with discontinuous task changes introduced in the fourth and seventh scenarios ( N  = 41 teams; 123 individuals). We applied pattern detection algorithm software to the behavioral data to identify emergent performative patterns in the team members' task‐oriented actions. We also used discontinuous growth modeling to track the development of these team action patterns and their dynamic relation to team effectiveness. The results indicate that pattern emergence increased over time. This was particularly true for teams with similar taskwork mental models, and these teams also showed a more acute decrease in action patterns after a task change. In addition, team action patterns became increasingly positively related to team effectiveness over time, but this effect was reset after the occurrence of a task change. Overall, our research provides practical guidance to managers by illustrating the value of teams having highly shared taskwork team mental models and of enhancing the effects of teams' action patterns on team adaptive outcomes.